Acrosomal integrity and HOS response at initial, post-thaw and post-refrigeration stages in Sephadex filtered Gir (Bos indicus) and Jafarabadi (Bubalus bubalis) bulls' semen - RANA, C M; DHAMI, A J (The Indian Journal of Animal Reproduction, 2023)
Split-samples of 40 ejaculates of 2 Girand 2 Jafarabadi bulls (10/bull) were initially filtered through 5 grades of sephadexgel columns (G-25, 50, 75, 100 & 200) to evaluate the relative efficacies of later towards improving the initial quality, freezabilityand storage ability (at 5°C) of semen in terms of acrosome integrity and HOS test. The mean percentages of sperms with intactacrosome recorded at initial, post-thaw (0 h) and post-refrigeration (48 h) stages were 84.15 ± 0.76, 69.33 ± 1.17 and 73. 78 ± 1.00in the unfiltered semen; 86.50 ± 0.79, 71.53 ± 1.00 and 76.60 ± 1.04 in the filtrates of sephadex G-25; 91.05 ± 0.62, 76.98 ± 0.92and 81.38 ± 0.90 in the filtrates of G-75; and 94.63 ± 0.64, 82.20 ± 0.86 and 86.35 ± 0.90 in the filtrates of G-200 columns,respectively. The corresponding values for HOS reactive sperm percent were 56.38 ± 1.91, 25.65 ± 1.52 and 32.98 ± 1.56 in theunfiltered semen; 59.90 ± 2.07, 28.50 ± 1.61 and 35.28 ± 1.60 in the filtrates of sephadex G-25; 68.05 ± 2.20, 36.05 ± 1.79 and43.30 ± 1.88 in G-75; and 75.87 ± 1.96, 42.55 ± 2.02 and 50.18 ± 2.13 in the filtrates of G-200 column. There was significant (P< 0.0 I) and progressive improvement in the percentage of sperms with intact anosome and HOS response with correspondingdecrease in the incidence of swollen, ruffled and denuded acrosome in the filtrates of 5 ascending grades of sephadex. The filtratesof 5 columns registered an increase in intact acrosome and HOS reactive sperms over controls by 2.79 • 12.45 and 6.24 • 34.57%initially, 3.17 • 18.56 and 6.94 - 59.66% at post-thaw stage and 3.82 - 17.04 and 6.97 - 52 .15 % at post-refrigeration stage,respectively. The influence of breeds (species), bulls, filtration treatments, breed x stage and breed x bull x stage interactions washighly significant (P < 0.01) for all the parameters, Semen quality, as assessed by acrosome integrity and HOS test, was much betterin filtrates of higher grades of sephadex (G-75 to G-200) than the lower grades (G-25, G-50) and in Gir than in Jafarabadi bulls andis expected to improve fertility also.
Keywords: Acrosomal integrity; HOS test; semen; Gir bulls; Jafarabadi buffalo; Sephadex filtration